2014
DOI: 10.3386/w20279
|View full text |Cite
|
Sign up to set email alerts
|

Typhoid Fever, Water Quality, and Human Capital Formation

Abstract: The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 0 publications
2
48
0
Order By: Relevance
“…For example, Nilsson () examines a change in alcohol policy that affected binge drinking, Schwandt (2017) examines the impact of contracting influenza during pregnancy (which is preventable by vaccination), and Isen, Rossin‐Slater, and Walker () examine the long‐term effect of having been exposed to higher levels of particulate air pollution in utero or in early childhood. In a developing country context, several authors have demonstrated the effects of reducing infectious disease (Baird, Hamory Hicks, Kremer, & Miguel, ; Beach, Ferrie, Saavedra, & Troesken, ; Bhalotra & Venkataramani, ) and improving nutrition (Adhvaryu, Bednar, Molina, Nguyen, & Nyshadham, ). In an important study, Gertler et al () examined the importance of attending to psychological needs by training mothers to provide psychosocial stimulation.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…For example, Nilsson () examines a change in alcohol policy that affected binge drinking, Schwandt (2017) examines the impact of contracting influenza during pregnancy (which is preventable by vaccination), and Isen, Rossin‐Slater, and Walker () examine the long‐term effect of having been exposed to higher levels of particulate air pollution in utero or in early childhood. In a developing country context, several authors have demonstrated the effects of reducing infectious disease (Baird, Hamory Hicks, Kremer, & Miguel, ; Beach, Ferrie, Saavedra, & Troesken, ; Bhalotra & Venkataramani, ) and improving nutrition (Adhvaryu, Bednar, Molina, Nguyen, & Nyshadham, ). In an important study, Gertler et al () examined the importance of attending to psychological needs by training mothers to provide psychosocial stimulation.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…Beach et al . () show that the use of water purification technologies to reduce typhoid had similar benefits for human capital. Another example is provided by Almond (), which documents the long‐term effects of the 1918 influenza pandemic.…”
mentioning
confidence: 97%
“…As these authors mention, some studies have found that for instance education, measured as compulsory schooling, reduces mortality in the United States, but not in England or France (see Cutler, Huang and Lleras-Muney (2015) and references therein). On the other hand, other studies such as Beach, Ferrie, Saavedra and Troesken (2016) examine how the declines of mortality rates due to new water purification technologies affected human capital formation. 27 We find similar results estimating equation (1) when the dependent variables (mortality measures) were specified by gender.…”
Section: Resultsmentioning
confidence: 99%